USING THE LATEST COMMUNICATION TOOLS AUTHORITIES AND THE PUBLIC - Lopatchenko, Ivan (Pressing Problems of Public Administration, 2021)
The article considers the importance of communication between the authorities and the public as an element of Ukraine’s development as a legal, democratic and social state. The current state of legislative regulation of communicative processes in the interaction of government and the public is analyzed. The main types, values, principles and tools of communication between the authorities and the public are clarified. The main tools of communication are identified: communication activities, newsletters, media, including press conferences, television and radio broadcasts, official websites, public hearings, social monitoring, work of advisory bodies, creation of working and expert groups, consultative portals, other platforms, as well as the latest social media, such as YouTube, Facebook, Twitter, Instagram, which, in our personal opinion, need special attention when using the latest communication tools in the interaction of government and the public. It was found that two thirds (67 %) of the adult population of Ukraine used the Internet. The share of users among people aged 18–45 in Ukraine reached 94 %. The number of Internet users continues to grow faster than expected. Between February 2014 and February 2018, the number of users increased by 12 percent. Such a comprehensive penetration of the Internet into modern life has created a huge potential for social networks. We believe that they should be used as an effective new tool for communication between the authorities and the public. An important task is to ensure comprehensive coordination of communication with the public both within one public authority and the executive branch as a whole, which will allow adequate and consistent presentation of government actions to the public and facilitate systematic feedback. That is why we see considerable potential in using the latest tools of communication between the authorities and the public to solve this problem. However, the use, as one of the main, of such a channel of communication in the activities of public administration, as social networks requires a more thorough theoretical understanding and further scientific analysis.